A Literature Survey on The Applications of Machine Learning Techniques in Medical and Bio- Informatics - Vinodh M R,; Sweety Bakyarani E, (AG Volumes, 2022)
Artificial Intelligence (AI) or Machine Learning (ML) have played a significant role in the fields of medical, Bio-informatics as well as clinical biology in recent years. From disease diagnostics to medical imaging to tumor detection to drug supplements etc. machine learning techniques have achieved a greater accuracy and precision at work. Researchers are still working to enhance and develop more accurate and precise techniques to cover more population samples as well as disease detection. This paper presents a literature survey on the applications of machine learning in the field of bio-medical and bio-informatics in the present scenario.